Molecular Bird Sexing of Small Yellow-crested Cockatoo (Cacatua sulphurea, Gmelin 1788) Using Polymerase Chain Reaction Method - Ratri, Inggit Nindika Dianing; Rahmawati, Irhamna Putri; Nugrahani, Warih Pulung; Haryanto, Aris (Universitas Gadjah Mada, Faculty of Biology, 2022)
The yellow-crested cockatoo (Cacatua sulphurea, Gmelin 1788) is an endemic bird in eastern part of Indonesia with monomorphic characteristics and included in the list of endangered birds. A method of sex determine in monomorphic birds is by molecular sexing which is based on the PCR amplification of the chromodomain helicase DNA-binding 1 (CHD-1) gene of the bird sex chromosome. This study was aimed to sex determine of the C. sulphurea by amplifying the CHD-1 gene on the Z and W chromosomes and comparing the PCR amplification results from peripheral blood and plucked feathers samples. The samples used were four birds of C. sulphurea from the Wildlife Rescue Centre (WRC), Yogyakarta. The feathers obtained from the ventral wings of each bird were plucked. Through the cutting of the birds' nails, the peripheral blood samples were collected into microhematocrit tubes which contained Heparin. The amplification of the CHD-1 gene used the PCR method with specific primers, such as NP, P2, and MP. Moreover, the PCR results were visualized on 1.5 agarose gel using UV-Transilluminator, at a wavelength of 280 nm. The PCR products (amplicons) were in 297 bp and 392 bp DNA bands, depending on the sex of the bird being tested. It was also observed that the male C. sulphurea produced single 392 bp DNA fragment of the Z chromosome. However, the female birds produced two DNA fragments of the Z and W chromosomes, with a length of 297 bp and 392 bp. The results showed that samples obtained from peripheral blood produced clearer DNA bands compared to plucked feather. It concludes that the extracted DNA from peripheral blood samples have a better quality compared to samples from plucked feathers. Amplification of the CHD-1 gene in male C. sulphurea generated only a single DNA fragment in size of 392 bp, so the four C. sulphurea were male birds. © 2022, J. Tropical Biodiversity Biotechnology.